Using a rhabdomyosarcoma patient‐derived xenograft to examine precision medicine approaches and model acquired resistance. Issue 9 (31st March 2014) - Monsma, David J.; Cherba, David M.; Richardson, Patrick J.; Vance, Sean; Rangarajan, Sanjeet; Dylewski, Dawna; Eugster, Emily; Scott, Stephanie B.; Beuschel, Nicole L.; Davidson, Paula J.; Axtell, Richard; Mitchell, Deanna; et al.
<x xml:space="preserve">Abstract</x> Background Precision (Personalized) medicine has the potential to revolutionize patient health care especially for many cancers where the fundamental disease etiology remains either elusive or has no available therapy. Here we outline a study in alveolar rhabdomyosarcoma, in which we use gene expression profiling and a series of drug prediction algorithms combined with a matched patient‐derived xenograft (PDX) model to test bioinformatically predicted therapies. Procedure A PDX model was developed from a patient biopsy and a number of drugs identified using gene expression analysis in combination with drug prediction algorithms. Drugs chosen from each of the predictive methodologies, along with the patient's standard‐of‐care therapy (ICE‐T), were tested in vivo in the PDX tumor. A second study was initiated using the tumors that re‐grew following the ICE‐T treatment. Further expression analysis identified additional therapies with potential anti‐tumor efficacy. Results A number of the predicted therapies were found to be active against the tumors in particular BGJ398 (FGFR2) and ICE‐T. Re‐transplanted ICE‐T treated tumorgrafts demonstrated a decreased response to ICE‐T recapitulating the patient's refractory disease. Gene expression profiling of the ICE‐T treated tumorgrafts identified cytarabine (SLC29A1) as a potential therapy, which was shown, along with BGJ398, to be highly active in vivo. Conclusions This study illustrates that PDX models are suitable surrogates for testing potential therapeutic strategies based on gene expression analysis, modeling clinical drug resistance and hold the potential to assist in guiding prospective patient care. Pediatr Blood Cancer 2014;61:1570–1577. © 2014 Wiley Periodicals, Inc.